An Antigen-Presenting and Apoptosis-Inducing Polymer Microparticle Prolongs Alloskin Graft Survival by Selectively and Markedly Depleting Alloreactive CD8+ T Cells - Wang, Wei; Shahzad, Khawar Ali; Li, Miaochen; Zhang, Aifeng; Zhang, Lei; Xu, Tao; Wan, Xin; Shen, Chuanlai (Frontiers in Immunology, 2017)
Selectively depleting the pathogenic T cells is a fundamental strategy for the treatment of allograft rejection and autoimmune disease since it retains the overall immune function of host. The concept of killer artificial antigen-presenting cells (KaAPC) has been developed by co-coupling peptide-major histocompatibility complex (pMHC) multimer and anti-Fas monoclonal antibody (mAb) onto the polymeric microparticles to induce the apoptosis of antigen-specific T cells. But little information is available about its in vivo therapeutic potential and mechanism. In this study, polyethylenimine (PEI)-coated poly lactic-co-glycolic acid microparticle (PLGA MP) was fabricated as a cell-sized scaffold to covalently co-couple H-2Kb-Ig dimer and anti-Fas mAb for the generation of alloantigen-presenting and apoptosis-inducing microparticle. Intravenous infusions of the biodegradable KaAPCs prolonged the alloskin graft survival for 43 days in a single MHC-mismatched murine model, depleted the most of H-2Kb-alloreactive CD8+ T cells in peripheral blood, spleen and alloskin graft in an antigen-specific manner and anti-Fas-dependent fashion. The cell-sized KaAPCs circulated throughout vasculature into liver, kidney, spleen, lymph nodes, lung, and heart, but few ones into local allograft at early stage, with a retention time up to 36 hours in vivo. They co-localized with CD8+ T cells in secondary lymphoid organs while few ones contacted with CD4+ T cells, B cells, macrophage, and dendritic cells, or internalized by phagocytes. Importantly, the KaAPCs treatment did not significantly impair the native T cell repertoire or nonpathogenic immune cells, did not obviously suppress the overall immune function of host, and did not lead to visible organ toxicity. Our results strongly document the high potential of PLGA MP-based KaAPCs as a novel antigen-specific immunotherapy for allograft rejection and autoimmune disorder. The in vivo mechanism of alloinhibition, tissue distribution, and biosafety were also initially characterized, which will facilitate its translational studies from bench to bedside.